2020
DOI: 10.15420/icr.2020.01
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotection for Acute MI in Light of the CONDI2/ERIC-PPCI Trial: New Targets Needed

Abstract: Protection against ischaemia–reperfusion injury after revascularisation in acute myocardial infarction remains an enigma. Many targets have been identified, but after the failure of the recent Effect of Remote Ischaemic Conditioning on Clinical Outcomes in ST-elevation Myocardial Infarction Patients Undergoing Primary Percutaneous Coronary Intervention (CONDI2/ERIC-PPCI) trial to show translation to clinical benefit, there is still no pharmacological or mechanical strategy that has translated to clinical pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 86 publications
(109 reference statements)
0
2
0
Order By: Relevance
“…A prior study using Troponin T showed similar findings as our current study with higher levels in those with poor coronary collaterals. 15,17 Studies by klopfer et al 19 and Habib et al 20 were also on similar lines.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…A prior study using Troponin T showed similar findings as our current study with higher levels in those with poor coronary collaterals. 15,17 Studies by klopfer et al 19 and Habib et al 20 were also on similar lines.…”
Section: Discussionmentioning
confidence: 56%
“…9,13,14 In fact, the biomarker value decreases as the collateral grade increases. 15,16,17 Our study is unique for analysing biomarkers sample being drawn at the time of angiogram. The study has given new insights into the impact of well-developed collaterals on traditional biomarker values in AMI patients in Asian Indian population.…”
Section: Discussionmentioning
confidence: 99%